Initial Contact with Forefoot or Rearfoot in Spastic Patients After Stroke—Three-Dimensional Gait Analysis - Inês Mendes-Andrade; Miguel Reis e Silva; Jorge Jacinto (Neurology International)
Background/Objectives: Post-stroke hemiparetic gait often presents with asymmetric patterns to compensate for stability deficits. This study examines gait differences in chronic stroke patients with spastic hemiparesis based on initial foot contact type—forefoot versus rearfoot. Methods: Thirty-four independently walking spastic hemiparetic patients were retrospectively analyzed. Using 3D gait analysis, patients were categorized by initial contact type. Spatiotemporal descriptors, joint kinematics, kinetics, and EMG patterns were compared across groups. Results: Patients with rearfoot initial contact (G1) showed higher cadence, longer single-limb support time and shorter stride times than those with forefoot contact (G0). G1 patients also demonstrated greater knee flexion during stance, enhancing stability. Additionally, G1 patients with abnormal lateral gastrocnemius activation in the swing phase showed increased ankle power at the end of the stance phase. Conclusions: In post-stroke spastic hemiparetic patients, the type of initial foot contact—forefoot or rearfoot—appears to influence gait characteristics, with rearfoot contact associated with a trend toward improved gait parameters, such as increased cadence and longer single-limb support.